Nurses Practice of Hand Hygiene in Hiwot Fana Specialized University Hospital, Harari Regional State, Eastern Ethiopia: Observational Study. (16th April 2018) - Awoke, Nefsu; Geda, Biftu; Arba, Aseb; Tekalign, Tiwabwork; Paulos, Kebreab
Abstract : Background . Nurses, who are the majority, can contaminate their hands with different types of microorganism during "clean" activities (e.g., lifting a patient; taking a patient's pulse, blood pressure, or oral temperature; or touching a patient's hand, shoulder, or groin). Yet good hand hygiene, the simple task of cleaning hands at the right time and in the right way, can reduce HCAIs that are transmitted by healthcare workers' hands. Method . Observational study conducted among nurses by observational tool which was adopted from WHO observational tool. And finally compliance was calculated as a percentage (i.e., compliance% = (observed hand hygiene action (HHA) ÷ hand hygiene opportunity (O)) × 100). The data were first coded, entered, and cleaned using EpiData statistical software version 3.1 and then exported into SPSS statistical software version 22 for analysis. Data were presented using descriptive statistics. Result . A total of 110 study participants were observed who gave a response rate of 94.8%. Total of 3902 opportunities and 732 hand hygiene actions were observed with overall compliance of 18.7%. The highest 22.9% hand hygiene practice was observed "before clean∖aseptic procedure." Highest 19.6% compliance was recorded at night shift and 22.7% in ICU ward of the hospital. Alcohol based hand rub was a major means of method used to clean hands. Conclusion and Recommendation . Observed practice of hand hygiene was poor. Lack of training, conveniently located sink, hand washing agents, and lack of time were major reasons for not practicing hand hygiene. Successful promotion of hand hygiene through instituting system change (e.g., making hand hygiene products available at the point of care) should be considered.